The Effect of Physical Effort On Some Motor Abilities Performance and Defensive Movement In Handball Players Aged 16 – 17 Years Old - Ghazi, Abdul wahaab; Hasson, Mortadha (Journal of Physical Education, 2019)
The importance of the research lies in finding new ways for training motor abilities on the development of skill level. The researchers used the experimental method on (10) handball players from the national center for gifted in handball. Many devices and tools were used like whistles, electronic watch, medical scale, tape, cones to conduct the tests. The data was collected and treated to come up with the conclusions and recommendations. The researchers recommended improving physical fitness in handball players as well as paying attention to motor abilities training and defensive movement after physical effort.